2008
DOI: 10.1534/genetics.108.087072
|View full text |Cite
|
Sign up to set email alerts
|

Cytotype Regulation of P Transposable Elements in Drosophila melanogaster: Repressor Polypeptides or piRNAs?

Abstract: The telomeric P elements TP5 and TP6 are associated with the P cytotype, a maternally inherited condition that represses P-element-induced hybrid dysgenesis in the Drosophila germ line. To see if cytotype repression by TP5 and TP6 might be mediated by the polypeptides they could encode, hobo transgenes carrying these elements were tested for expression of mRNA in the female germ line and for repression of hybrid dysgenesis. The TP5 and TP6 transgenes expressed more germ-line mRNA than the native telomeric P el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Transgenes encoding both type I (Robertson and Engels 1989;Misra and Rio 1990;Rasmusson et al 1993) and type II repressors (Gloor et al 1993;Simmons et al 2002;Jensen et al 2008) reduce the excision rate of P elements in vivo. Although the precise mechanism of repressor protein action remains unclear, they are posited to act as competitive inhibitors of P transcription.…”
Section: Germline Regulation By Repressor Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Transgenes encoding both type I (Robertson and Engels 1989;Misra and Rio 1990;Rasmusson et al 1993) and type II repressors (Gloor et al 1993;Simmons et al 2002;Jensen et al 2008) reduce the excision rate of P elements in vivo. Although the precise mechanism of repressor protein action remains unclear, they are posited to act as competitive inhibitors of P transcription.…”
Section: Germline Regulation By Repressor Proteinsmentioning
confidence: 99%
“…However, recent research has revealed that the piRNA pathway is the molecular basis of cytotype regulation (Reiss et al 2004;Brennecke et al 2008;Jensen et al 2008;Belinco et al 2009;Khurana et al 2011). Indeed, P-cytotype genetics and piRNA-mediated silencing are increasingly synergistic, with classic observations motivating modern molecular experiments and new mechanisms shedding light on old discoveries.…”
Section: Dissecting the P Cytotype: From Classical Genetics To Pirnasmentioning
confidence: 99%
See 3 more Smart Citations